2002
DOI: 10.1002/oa.615
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of cribra orbitalia in the subadult medieval population from Gruczno, Poland

Abstract: The purpose of this work is to present data on the frequency of cribra orbitalia in the skulls of children from a Polish medieval population cemetery in Gruczno and to compare the results with the frequency of this phenomenon in adult populations. The frequency of cribra orbitalia was investigated in 92 skulls belonging to individuals who died between the ages of 0 to 15 years. The Hengen scale (1971) and the Nathan & Haas scale (1966) as modified by Robledo et al. (1995) were used. The frequency of cribra orb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
3
9
0
1
Order By: Relevance
“…There was a similar fi nding by Beňuš et al (2010) on several Slavic samples, where there was an increase in cribra orbitalia among the 1-4 years age group and 5-9 years. In further studies from medieval Poland, high levels of cribra orbitalia was observed in those aged 0-7 (47%) and 7-15 years (50%) (Piontek and Kozlowski, 2002). The same happened in studies from Roman Italy (Facchini et al, 2004).…”
Section: Discussionsupporting
confidence: 54%
“…There was a similar fi nding by Beňuš et al (2010) on several Slavic samples, where there was an increase in cribra orbitalia among the 1-4 years age group and 5-9 years. In further studies from medieval Poland, high levels of cribra orbitalia was observed in those aged 0-7 (47%) and 7-15 years (50%) (Piontek and Kozlowski, 2002). The same happened in studies from Roman Italy (Facchini et al, 2004).…”
Section: Discussionsupporting
confidence: 54%
“…What emerges most poignantly from this analysis, and others like it, is that any nuanced etiological understanding of anemia, past or present, must pay close attention to the physiological, environmental, social, cultural, political, and economic conditions in which people live their lives (Fairgrieve and Molto, 2000;Gleń -Haduch et al, 1997;Keenleyside, 1998;Keita and Boyce, 2001;Lovell, 1997;Papathanasiou et al, 2000;Pechenkina et al, 2002;Pietrusewsky et al, 1997;Piontek and Kozlowski, 2002;Salvadei et al, 2001;Š laus, 2000;Stodder, 1997;Walker, 1986). Since individual and collective experiences of health and disease vary along all of these axes, it is perhaps not surprising that the important biocultural axes of age, sex, and status explored here show complex relationships to the presence and etiology of anemia as measured by cribra orbitalia.…”
Section: Discussionmentioning
confidence: 96%
“…Harris lines tend to occur in great numbers in medieval subadults, commonly exceeding 80% (Gronkiewicz et al 2001;Łubocka 2003;Havelková et al 2008;Piontek 2014), which was also true for our samples, in contrast to lower rates found in some other European studies (Lewis 2002). Cribra orbitalia in child remains commonly ranges from 40% to 60% (Šlaus 2000;Piontek and Kozłowski 2002;Bennike et al 2005;Kwiatkowska 2005;Djuric et al 2008;Velemínský et al 2009;Kozłowski 2012;Novak et al 2012;Piontek 2014), although the subadults from Cedynia showed an elevated rate of this condition, similar to a sample from Slovakia (Obertová and Thurzo 2004). The high cribra orbitalia frequencies in children are not surprising.…”
Section: Nonspecific Stressmentioning
confidence: 65%